Design, fabrication, and characterization of bridge-type micro-hotplates with an SU-8 supporting layer for a smart gas sensing system. (11th January 2017) - Iwata, T; Soo, W P C; Matsuda, K; Takahashi, K; Ishida, M; Sawada, K
Abstract: In this study, bridge-type micro-hotplates (MHP) with an SU-8 supporting layer were proposed for smart gas sensor applications. The proposed MHP consisted of a heating membrane with an area of 140 µ m × 140 µ m, and a 33 µ m-thick SU-8 layer deposited on its bridges. Finite element method based simulation confirmed that the proposed MHP displayed good thermal isolation properties. The proposed MHP was successfully fabricated, and the properties of the MHP were characterized. Current–voltage characteristics revealed that the MHP temperature can reach 550 °C at 5 V. The temperature of the MHP was calculated from changes in the resistance of the heater. Power consumption of the MHP approximately corresponded to 13.9 mW for heating to 300 °C. This was comparable to the power consumption reported in the previous studies. Furthermore, a stable operation under a constant voltage was observed for 100 min. The properties of the MHP indicated that it could potentially be utilized for applications related to integrated gas sensors.